Association between Immediate Breast Reconstruction and the Development of Breast Cancer–Related Lymphedema. Issue 2 (8th November 2022) - Jeon, Hong Bae; Jung, Ji Hyuk; Im, Sang Hee; Kim, Yong Bae; Chang, Jee Suk; Song, Seung Yong; Lew, Dae Hyun; Roh, Tai Suk; Lee, Won Jai; Lee, Dong Won
Abstract : Background: With the increasing number of patients undergoing immediate breast reconstruction after mastectomy, the impact of immediate breast reconstruction on the risk of breast cancer–related lymphedema has become an emerging area of interest. This study aimed to identify the association between immediate breast reconstruction and postoperative lymphedema. Methods: A retrospective cohort study was conducted from 2006 to 2016 with 5900 consecutive patients who underwent mastectomy for primary breast cancer with or without immediate breast reconstruction. After excluding patients with synchronous contralateral breast cancer, lymphedema before mastectomy, history of procedures performed in the axillary region, and follow-up data of less than 1 year, the cumulative incidence of lymphedema after immediate breast reconstruction and after no reconstruction was calculated and compared using multivariate Cox regression analysis. Results: Overall, 5497 patients (mean age, 51.7 years) were included, and 630 developed lymphedema. The 5-year cumulative incidence rate of lymphedema was significantly reduced in patients who underwent immediate breast reconstruction versus control patients (9.6% versus 12.2%; P = 0.02). In the multivariate analysis, immediate breast reconstruction status (hazard ratio, 0.75; 95% confidence interval, 0.56 to 0.99; P = 0.042) was an independent predictor for lymphedema. Similar significant associations were observed in the subgroup analyses of patients with a body mass index less than 30 kg/m 2 ( P = 0.024), in those with fewer than 10 dissected lymph nodes ( P = 0.042), or in those with adjuvant radiotherapy ( P = 0.048). Conclusions: Immediate breast reconstruction was associated with a reduced risk of lymphedema. These results may be used for predicting the development of lymphedema following breast reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.